The Role of Sharia Marketing in Increasing Customer Loyalty (An Empirical Study of BMT in Kudus Regency) - Rahmawaty, Anita; Rokhman, Wahibur (Ekonomi Syariah IAIN Kudus, 2018)
This research strives to empirically examine and analyze the influence of syariah marketing and service quality on BMT customer loyalty and satisfaction in Kudus Regency. This study was a survey research that used a quantitative approach. The research data were obtained from 250 BMT customers within Kudus Regency by using an accidental sampling technique. Meanwhile, the data analysis used a path analysis technique. The research findings revealed that: first, sharia marketing has a positive and significant influence on customer satisfaction; second, service quality has a positive and significant influence on customer satisfaction; third, sharia marketing has a positive and significant influence on customer loyalty; fourth, service quality has a positive and significant influence on customer loyalty; and fifth, customer satisfaction has a positive and significant influence on customer loyalty.